2021
DOI: 10.1007/s00125-021-05545-w
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes concomitant to aortic stenosis is associated with increased expression of NF-κB and more pronounced valve calcification

Abstract: Aims/hypothesis Type 2 diabetes has been demonstrated to predispose to aortic valve calcification. We investigated whether type 2 diabetes concomitant to aortic stenosis (AS) enhances valvular inflammation and coagulation activation via upregulated expression of NF-κB, with subsequent increased expression of bone morphogenetic protein 2 (BMP-2). Methods In this case–control study, 50 individuals with severe isolated AS and concomitant type 2 diabetes were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Similar results were obtained by Larsson et al [8], who have shown that type 2 DM was associated with a 34% increased risk of AS and Martinsson et al [51], who have reported DM as an independent risk factor for AS development. On the other hand, Testuz et al [9] have failed, during a 3-year follow-up, to observe the association between AS progression and metabolic syndrome or diabetes; however, in this study only fasting glucose levels were analyzed while it has been shown that long-term glycemic control may be of key importance [10,11].…”
Section: Clinical Trials On Dm Influence On As Development and Progressionmentioning
confidence: 90%
See 4 more Smart Citations
“…Similar results were obtained by Larsson et al [8], who have shown that type 2 DM was associated with a 34% increased risk of AS and Martinsson et al [51], who have reported DM as an independent risk factor for AS development. On the other hand, Testuz et al [9] have failed, during a 3-year follow-up, to observe the association between AS progression and metabolic syndrome or diabetes; however, in this study only fasting glucose levels were analyzed while it has been shown that long-term glycemic control may be of key importance [10,11].…”
Section: Clinical Trials On Dm Influence On As Development and Progressionmentioning
confidence: 90%
“…Interestingly, both the quantity of fibrin and the degree of valve calcification correlated with factor (F)XIII expression derived mainly from the alternatively activated macrophages recruited to the valve leaflets [29]. Recently, it has been shown that VICs are also able to express prothrombin and active FX [11]. Moreover, growing evidence indicates that AS patients are characterized by impaired clot susceptibility to fibrinolysis [33,34], the process closely regulated by specific inhibitors, such as plasminogen activator inhibitor type-1 and thrombin-activatable fibrinolysis inhibitor [35].…”
Section: Pathomechanisms Of Degenerative Asmentioning
confidence: 99%
See 3 more Smart Citations